High current density photocathode for CW terahertz photoconductive vacuum devices. (October 2020) - Dai, Jun; Ruan, Cunjun; Xu, Xiangyan; Liu, Hulin; Ding, Yikun
Abstract: For vacuum electronics-related terahertz (THz) sources, robust, quick-response, and tunable continuous emission electron emitters are still challenging. In this paper, a continuous emission high current density Na2 KSb(Cs) photocathode is developed and verified experimentally. The photocathode emission enhancement is achieved through optimization of film thickness, adjustment of the cesium activation, and dynamic optimization of the quantum efficiency during the synthesis process. The detailed evaporation procedures to perform the photocathode growth is investigated and reported. To maintain a higher current density, performances of photocathode evaporated on borosilicate glass and sapphire are tested respectively and analyzed comparatively. The results show that remarkable continuous current density can be achieved at 30 mA/cm 2 on glass substrates, and 3 A/cm 2 on sapphire substrates respectively. We found that the thermal conductivity of the substrates has a significant impact on high current density operations. The optimal emission current density has reached a promising value for future excitation of continuous wave (CW) THz wave radiation based on the photoconductive vacuum devices. These results also offer an opportunity to approach the generation and temporal shaping of planar array electron beams for THz vacuum tubes. Highlights: Develop and experimentally verify a continuous emission high current density Na2 KSb(Cs) photocathode. Dynamic optimization of the quantum efficiency during the synthesis process. 30 mA/cm 2 on glass substrates, 3 A/cm 2 on sapphire substrates. Thermal conductivity of the substrates influences high current density operations.